Denying Access to Legal Representation: The Attack on the Tulane Law Clinic - Robert R. Kuehn (Washington University Journal of Law & Policy, 2000)
When people require assistance to advance public interests, rather than private interests, the lack of legal representation is even more severe—less than .001% of lawyers in the legal profession are public interest lawyers. “Although recent data are unavailable, the best available estimates suggest that the number of full-time public interest lawyers is less than one attorney for every 240,000 Americans.” Citizens advancing issues of public concern often have no choice but to turn for free assistance from law school professors or one of the nation’s law school clinics.
Keywords: Environmental justice; Law schools; Legal assistance to the poor; Right to counsel; Tulane University. School of Law